Radioactive element adsorbent containing magnesium silicate and its manufacturing method

A magnesium silicate-based adsorbent optimizes cesium, cobalt, and strontium removal from nuclear waste, enhancing nuclear waste disposal and plant efficiency through controlled pore size and composition, achieving high removal efficiencies.

JP7599747B2Active Publication Date: 2024-12-16GIANT CHEM CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023196740
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-09-18
Filing Date
2023-11-20
Publication Date
2024-12-16
Estimated Expiration
2043-11-20

AI Technical Summary

Technical Problem

Existing methods struggle to efficiently remove radioactive cesium, cobalt, and strontium from nuclear waste due to their high solubility and reactivity, which poses health risks and reduces nuclear power plant efficiency.

Method used

A radioactive element adsorbent comprising magnesium silicate with controlled pore size and elemental composition is developed, optimized for cesium, cobalt, and strontium removal, produced through a method involving silicate precursor preparation, mixing with a magnesium precursor and ammonium salt, and reaction at controlled temperatures.

Benefits of technology

The adsorbent achieves high removal efficiencies of 95-100% for cesium, 95-100% for cobalt, and 95-100% for strontium, improving nuclear waste disposal and plant efficiency by reducing hazardous elements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007599747000010
    Figure 0007599747000010
  • Figure 0007599747000011
    Figure 0007599747000011
  • Figure 0007599747000012
    Figure 0007599747000012
Patent Text Reader

Abstract

To provide a radioactive element adsorbent containing magnesium silicate and a method of manufacturing the same.SOLUTION: The present invention relates to a magnesium silicate-containing adsorbent for radioactive elements such as cesium, cobalt, and strontium, and a method of manufacturing the same. The present invention can specify the pore size, MgO content, and SiO2 content of the magnesium silicate that optimize radioactive element adsorption efficiency.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a radioactive element adsorbent containing magnesium silicate and a method for producing the same, and more particularly to a radioactive element adsorbent containing magnesium silicate for cesium, cobalt and strontium and a method for producing the same. [Background technology]

[0002] Nanoporous materials with large specific surface areas and uniform pores are widely used as adsorbents, catalyst supports, separation and purification processes, and ion exchange media. In particular, the synthesis of novel nanostructured materials with controlled porosity is an ongoing area of ​​research in the field of new materials.

[0003] Magnesium silicate, in particular, is a porous inorganic chemical substance synthesized by a precipitation reaction between water soluble magnesium salts and sodium silicate. Due to its strong adsorption properties, it is used in industrial applications, food refining, cosmetics raw materials, and other fields.

[0004] Meanwhile, as the world becomes increasingly dependent on nuclear power plants for energy, the disposal of radioactive waste that may result from a nuclear accident has emerged as a major issue.

[0005] Radioactive cesium ( 137 Cs is the main cause of radioactive contamination from nuclear power plant accidents, nuclear waste, etc. It has high solubility in water, a long half-life, and behaves similarly to potassium ions in the body, so even if it is absorbed into the body it is not excreted properly and can cause various cancers, including lung cancer and bone marrow cancer. Therefore, there is an emerging need for technology to remove this radioactive cesium.

[0006] Cobalt (Co) is a radioactive nuclide that does not exist in nature, and when exposed to high temperature and pressure during the operation of a nuclear power plant, it reacts with water and dissolved oxygen to form corrosion products, and together with radioactive materials emitted from the nuclear fuel, it forms an oxide film on the cooling water pipeline. The oxide film formed at this time is made up of components of the coolant contact equipment, such as iron, chromium, nickel, copper, and cobalt, and reduces the efficiency of heat transfer required for cooling, causing a decrease in the operating efficiency of the nuclear power plant.

[0007] Strontium (Sr) is a soft, silvery-white alkaline earth metal that is softer and more reactive than calcium. It reacts violently in water to produce strontium hydroxide (Sr(OH)2) and hydrogen gas (H2), and burns in air to produce strontium oxide and strontium nitride. Cesium and strontium are radioactive contaminant nuclides that are formed in large quantities during the nuclear fission of uranium, and because they have the property of releasing high amounts of heat and a half-life of more than 30 years, they must be removed from radioactive contaminated water.

[0008] However, radioactive liquid waste contains various chemical substances, and due to foaming and corrosion during operation, the operating conditions are strict and smooth processing is difficult. Therefore, methods using adsorbents to efficiently remove radioactive elements are being considered. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] Korean Patent Registration No. 10-2221740 Summary of the Invention [Problem to be solved by the invention]

[0010] An object of the present invention is to provide a radioactive element adsorbent comprising magnesium silicate capable of adsorbing cesium, cobalt and strontium.

[0011] Another object of the present invention is to specify the pore size, MgO and SiO2 contents of said magnesium silicate which can optimize the cesium removal efficiency.

[0012] It is still another object of the present invention to provide a method for producing the cesium, cobalt and strontium radioactive element adsorbent containing said magnesium silicate.

[0013] The technical problems that the present invention aims to solve are not limited to the technical problems mentioned above, and other technical problems not mentioned will also be clearly understood by a person having ordinary skill in the art from the description of the present invention. [Means for solving the problem]

[0014] The present invention provides a radioactive element adsorbent comprising magnesium silicate.

[0015] In the present invention, the radioactive element is one or more elements selected from the group consisting of cesium, cobalt, and strontium.

[0016] In the present invention, the magnesium silicate is characterized in that the pore size is 33 to 40 Å.

[0017] In the present invention, the magnesium silicate is characterized in that the MgO content is reduced by 3 to 4% and the SiO2 content is increased by 8 to 8.5% compared to magnesium silicate according to the USP / NF standard.

[0018] In the present invention, the magnesium silicate is characterized in that it contains 14.4 to 14.6 parts by weight of MgO and 72.4 to 72.6 parts by weight of SiO2 relative to 100 parts by weight of the magnesium silicate.

[0019] The present invention also provides a method for producing a radioactive element adsorbent containing magnesium silicate, comprising the steps of: (A1) producing a silicate precursor; (A2) mixing a magnesium precursor with an ammonium salt to produce a mixture; and (A3) adding the silicate precursor to the mixture to produce a radioactive element adsorbent containing magnesium silicate.

[0020] In the present invention, the magnesium precursor is characterized in that it is magnesium chloride (MgCl2). Effect of the Invention

[0021] The present invention can provide a radioactive element adsorbent containing magnesium silicate capable of adsorbing cesium, cobalt and strontium.

[0022] In addition, the present invention can embody the pore size of the magnesium silicate and the contents of MgO and SiO2 that can optimize the adsorption efficiency of radioactive elements.

[0023] Furthermore, the present invention can provide a method for producing an adsorbent for radioactive elements of cesium, cobalt and strontium, which contains the magnesium silicate.

[0024] The effects of the present invention are not limited to those mentioned above, and other effects not mentioned will be clearly understood by those skilled in the art from the description of the claims. [Brief description of the drawings]

[0025] [Figure 1] 1 is a photograph showing the color change of magnesium silicate according to the present invention after cesium adsorption. [Diagram 2] 1 is a photograph showing the color change of magnesium silicate according to the present invention after adsorption of cobalt. [Diagram 3] 1 is a photograph showing the color change of magnesium silicate according to the present invention after strontium adsorption. [Figure 4] FIG. 2 is a schematic diagram showing the adsorption mechanism of radioactive elements by magnesium silicate according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0026] The terms used in this specification are selected as widely used as possible while taking into consideration the functions of the present invention, but they may vary depending on the intentions of those skilled in the art, precedents, or the emergence of new technology. In addition, in certain cases, the applicant may arbitrarily select a term, and in such cases, the meaning of the term will be described in detail in the description of the invention. Therefore, the terms used in this specification are defined based on the meaning of the term and the overall content of the present invention, rather than simply the name of the term.

[0027] Unless otherwise defined, all terms used herein, including technical or scientific terms, have the same meaning as commonly understood by a person of ordinary skill in the art to which this invention pertains. Terms as defined in commonly used dictionaries should be interpreted to have a meaning consistent with the meaning they have in the context of the relevant art, and should not be interpreted as idealized or overly formal unless expressly defined in this application.

[0028] Numeric ranges are inclusive of the numerical values ​​defined in the range. Every maximum numerical limitation given herein includes every lower numerical limitation, as if a lower numerical limitation is expressly stated. Every minimum numerical limitation given herein includes every higher numerical limitation, as if a higher numerical limitation is expressly stated. Every numerical limitation given herein includes every greater numerical range within a broader numerical range, as if a narrower numerical limitation is expressly stated.

[0029] The present invention will be described in detail below.

[0030] Radioactive element adsorbents containing magnesium silicate The present invention provides a radioactive element adsorbent comprising magnesium silicate.

[0031] The radioactive element may be one or more selected from the group consisting of cesium, cobalt, and strontium.

[0032] The pore size of the magnesium silicate may be 33 to 40 Å, preferably 34 to 38 Å.

[0033] The weight of the magnesium silicate may be 0.15 to 0.25 g, preferably 0.19 to 0.21 g.

[0034] The specific surface area of ​​the magnesium silicate is 40 to 60 m 2 / g, preferably 43 to 50m 2 / g.

[0035] The pore volume of the magnesium silicate is 0.02 to 0.1 cm 3 / g, preferably 0.02 to 0.06 cm 3 / g.

[0036] The cesium removal efficiency of the magnesium silicate may be 95 to 100%, preferably 97 to 100%. The cesium removal efficiency may be calculated according to the following formula 1, in which C i is the initial metal ion concentration, and C f may be the metal ion concentration after adsorption.

[0037] Similarly, the cobalt removal efficiency of the magnesium silicate may be 95 to 100%, preferably 98 to 100%. The cobalt removal efficiency may be calculated according to the following formula 1, where C i is the initial metal ion concentration, and C f may be the metal ion concentration after adsorption.

[0038] Similarly, the strontium removal efficiency of the magnesium silicate may be 95 to 100%, preferably 96 to 100%. The strontium removal efficiency may be calculated according to the following formula 1, in which C i is the initial metal ion concentration, C f may be the metal ion concentration after adsorption.

[0039]

number

[0040] The magnesium silicate may have an elemental silicon (Si) content of 70-80%, a magnesium (Mg) content of 18-25%, and a ratio of Mg:Si of 1:3-4.

[0041] The magnesium silicate may be characterized in that it contains 14.4 to 14.6 parts by weight of MgO and 72.4 to 72.6 parts by weight of SiO2 relative to 100 parts by weight of the magnesium silicate.

[0042] The magnesium silicate may be characterized by a 3-4% decrease in MgO content and an 8-8.5% increase in SiO2 content compared to USP / NF standard magnesium silicate, and preferably by a 3.2-3.4% decrease in MgO content and an 8.1-8.3% increase in SiO2 content compared to USP / NF standard magnesium silicate.

[0043] The USP / NF magnesium silicate may be characterized by an MgO content of 15% and an SiO2 content of 67%.

[0044] Method for producing radioactive element adsorbent containing magnesium silicate The present invention provides a method for producing a radioactive element adsorbent comprising magnesium silicate.

[0045] The present invention provides a method for producing a radioactive element adsorbent containing magnesium silicate, comprising the steps of: (A1) producing a silicate precursor; (A2) mixing a magnesium precursor with an ammonium salt to produce a mixture; and (A3) adding the silicate precursor to the mixture to produce a radioactive element adsorbent containing magnesium silicate.

[0046] The step (A1) is a step of preparing a silicate precursor, which may be prepared by adding tetraethyl orthosilicate (TEOS) to a mixture of alcohol, water, and aqueous ammonia (NH3H2O, ammonia-water), and stirring the mixture at 200-300 rpm for 1-3 hours after adding the tetraethyl orthosilicate. The mixture is centrifuged and then dried at 60-80°C to prepare the silicate precursor.

[0047] The silicate precursor may be at least one selected from the group consisting of silica (SiO2), sodium silicate, tetramethyl orthosilicate, tetraethyl orthosilicate, tetrapropyl orthosilicate, triethoxyethylsilane (TEES), and 1,2-bis(triethoxysilyl)ethane (BTSE).

[0048] The step (A2) is a step of mixing a magnesium precursor and an ammonium salt to prepare a mixture, and the magnesium precursor may be one or more selected from the group consisting of magnesium nitrate (Mg(NO3)2), magnesium sulfate (MgSO4), and magnesium chloride (MgCl2), and the magnesium precursor may be a single precursor or a mixed precursor. The ammonium salt may be one or more selected from the group consisting of ammonium chloride (NH4Cl), ammonium nitrate (NH4NO3), and ammonium sulfate ((NH4)2SO4).

[0049] More specifically, in step (A2), the magnesium precursor and the ammonium salt are dissolved in distilled water, and then aqueous ammonia (NH4OH) is added to prepare a mixture. Preferably, magnesium chloride (MgCl2) and ammonium chloride (NH4Cl) are dissolved in distilled water, and then 23 to 33% aqueous ammonia is added to prepare a mixture.

[0050] The step (A3) is a step of adding the silicate precursor to the mixture to produce a radioactive element adsorbent containing magnesium silicate. More specifically, in the step (A3), the silicate precursor is dispersed in distilled water, and the dispersion is added to a mixture of the magnesium precursor, ammonium salt and ammonia water to homogenize it, and then the homogenized material is reacted at 120 to 160 ° C for 10 to 14 hours to release Si ions of spherical silica (SiO2) which is a silicate precursor, and an interaction between the released Si ions and magnesium ions can be induced. Next, the reactant which has completed the interaction is cooled and dried at a temperature of 60 to 80 ° C to produce magnesium silicate having radioactive element adsorption ability.

[0051] EXAMPLES The present invention will be described in detail below with reference to examples, but it goes without saying that the present invention is not limited to these examples.

[0052] Example 1. Preparation of radioactive element adsorbent containing magnesium silicate 1-1. Preparation of silicate precursor Ethanol, distilled water and aqueous ammonia (NH3H2O, ammonia-water) were mixed homogeneously, and tetraethyl orthosilicate (TEOS) was added to the mixture of ethanol, distilled water and aqueous ammonia, and stirred at room temperature for 2 hours at a speed of 250 rpm. The mixture after stirring was centrifuged at high speed to separate the solid layer, which was washed with distilled water and ethanol and then dried at 70°C to produce microsilica (SiO2), a silicate precursor having micro-sized particles.

[0053] 1-2. Manufacturing of radioactive element adsorbents containing magnesium silicate For the production of magnesium silicate with radioactive element adsorption performance, a silicate precursor having particles with appropriate specific surface area, pore volume and pore size was prepared by the Stober process using spherical silica (SiO2) as the silicate precursor.

[0054] Magnesium chloride (MgCl2, 0.75 mmol) and ammonium chloride (NH4Cl, 10 mmol) were dissolved in 30 mL of distilled water, and then 1 mL of 28% aqueous ammonia (NH4OH) was added and mixed to prepare a mixture. 0.1 g of the prepared sodium silicate having micro-sized particles was dispersed in 20 mL of distilled water, and the dispersion was added to the mixture and mixed until homogeneous. The homogeneous material was transferred to an autoclave and reacted at 140°C for 12 hours to release Si ions of spherical silica (SiO2), which is a silicate precursor, and react for interaction between the released Si ions and magnesium ions. Thereafter, the reactant was cooled to room temperature, and then the magnesium silicate produced by the reaction was filtered, washed with distilled water, and dried in a dryer at 70°C to prepare magnesium silicate having radioactive element adsorption ability.

[0055] Comparative Example 1. Preparation of magnesium silicate with adjusted molar amount of magnesium chloride In order to confirm the radioactive element adsorption capacity according to the molar amount of magnesium chloride, magnesium silicate was produced by adjusting the molar amount of magnesium chloride from 0.75 mmol to 0.62 mmol. This magnesium silicate was produced in the same manner as the magnesium silicate in Example 1, except for the molar amount of magnesium chloride.

[0056] Comparative Example 2. Production of illite In the case of illite, it is usually first extracted from the mine and then processed through a separate crushing and drying process.

[0057] Experimental Example 1. Analysis of the specific surface area of ​​magnesium silicate Experimental Example 1 was carried out to perform specific surface area analysis (BET) of the magnesium silicate and illite prepared in Example 1, Comparative Example 1, and Comparative Example 2. The results of Experimental Example 1 are shown in Table 1.

[0058] As a result of Experimental Example 1, it was confirmed that the pore diameter of the magnesium silicate prepared in Example 1 was 35.279 Å, the pore diameter of the magnesium silicate prepared in Comparative Example 1 was 78.932 Å, and the pore diameter of the illite prepared in Comparative Example 2 was 115.30 Å.

[0059] The specific surface area of ​​the magnesium silicate prepared in Example 1 is 46.0530 m 2 / g, and the specific surface area of ​​the magnesium silicate prepared in Comparative Example 1 is 206.1126 m 2 / g, and the specific surface area of ​​the illite prepared in Comparative Example 2 was 10.1502 m 2 / g.

[0060] The pore volume of the magnesium silicate prepared in Example 1 was 0.0406 cm 3 / g, and the pore volume of the magnesium silicate prepared in Comparative Example 1 was 0.4057 cm3 / g, and the pore volume of the illite prepared in Comparative Example 2 was 0.0292 cm 3 / g.

[0061] [Table 1]

[0062] Experimental Example 2. Cesium removal efficiency of magnesium silicate Experimental Example 2 was carried out to examine the cesium (Cs) removal efficiency of the magnesium silicate and illite prepared in Example 1, Comparative Example 1 and Comparative Example 2.

[0063] 126 mg of cesium chloride was dissolved in 1 L of distilled water and dispersed for 10 minutes using ultrasonic vibration. 100 mL of the dispersion was stirred at 300 rpm, and 1 g each of the magnesium silicate or illite adsorbent prepared in Example 1, Comparative Example 1, or Comparative Example 2 was added. The mixed solution of the dispersion and the adsorbent was centrifuged at 8000 rpm for 5 minutes to separate the supernatant. The residual cesium concentration of the supernatant was confirmed by inductively coupled plasma-mass spectrometry (ICP-MS), and the results of Experimental Example 2 are shown in Table 2 below.

[0064] As a result of Experimental Example 2, the cesium removal efficiency of Example 1 was 98.84%, the cesium removal efficiency of Comparative Example 1 was 80.60%, and the cesium removal efficiency of Comparative Example 2 was 79.0%. The cesium removal efficiency was calculated according to the following formula 1, where C i is the initial metal ion concentration, and C f means the metal ion concentration after adsorption.

[0065]

number

[0066] [Table 2]

[0067] Experimental Example 3. Color change of magnesium silicate after cesium adsorption Experimental Example 3 was carried out to observe the color change of the magnesium silicate and illite produced in Example 1, Comparative Example 1 and Comparative Example 2 after cesium adsorption. The cesium adsorption method using the magnesium silicate or illite was carried out in the same manner as in Experimental Example 2. The results of observing the color change of the magnesium silicate and illite after cesium adsorption are shown in FIG.

[0068] As a result of this Experimental Example 3, no change in color was observed after cesium adsorption in any of the magnesium silicates and illite of Example 1, Comparative Example 1, and Comparative Example 2 (FIG. 1).

[0069] Experimental Example 4. Comparison of cobalt removal efficiency of magnesium silicates Experimental Example 4 was carried out to confirm the cobalt removal efficiency of the magnesium silicates and illite prepared in Example 1, Comparative Example 1 and Comparative Example 2.

[0070] 493.8 mg of cobalt nitrate was dissolved in 1 L of distilled water and dispersed for 10 minutes using ultrasonic vibration. 100 mL of the dispersion was stirred at 300 rpm, and 1 g of each of the magnesium silicate or illite adsorbent prepared in Example 1, Comparative Example 1, or Comparative Example 2 was added. The mixed solution of the dispersion and the adsorbent was centrifuged at 8000 rpm for 5 minutes to separate the supernatant. The residual cobalt concentration of the supernatant was confirmed by inductively coupled plasma-mass spectrometry (ICP-MS), and the results of Experimental Example 4 are shown in Table 3 below.

[0071] As a result of Experimental Example 4, the cobalt removal efficiency was 99.98% in Example 1, 99.97% in Comparative Example 1, and 10.1% in Comparative Example 2. The cobalt removal efficiency was calculated according to Equation 1.

[0072] [Table 3]

[0073] Experimental Example 5. Color change after adsorption of cobalt onto magnesium silicate Experimental Example 5 was carried out to observe the color change of the magnesium silicate and illite prepared in Example 1, Comparative Example 1 and Comparative Example 2 after adsorbing cobalt. The method of adsorbing cobalt using the magnesium silicate according to Example 1 was carried out in the same manner as in Experimental Example 4. The color change of the magnesium silicate after adsorbing cobalt is shown in FIG.

[0074] As a result of Experimental Example 5, the magnesium silicate of Example 1 changed color from white to light gray with a greenish tinge after adsorbing cobalt, while no color change was observed in the magnesium silicate of Comparative Example 1 and the illite of Comparative Example 2 (FIG. 2).

[0075] Experimental Example 6. Comparison of strontium removal efficiency of magnesium silicate Experimental Example 6 was carried out to confirm the strontium removal efficiency of the magnesium silicates and illite prepared in Example 1, Comparative Example 1 and Comparative Example 2.

[0076] 180.9 mg of strontium chloride was dissolved in 1 L of distilled water and dispersed for 10 minutes using ultrasonic vibration. 100 mL of the dispersion was stirred at 300 rpm, and 1 g of each of the magnesium silicate or illite adsorbent prepared in Example 1, Comparative Example 1, or Comparative Example 2 was added. The mixed solution of the dispersion and the adsorbent was centrifuged at 8000 rpm for 5 minutes to separate the supernatant. The residual strontium concentration of the supernatant was confirmed by inductively coupled plasma-mass spectrometry (ICP-MS), and the results of Experimental Example 6 are shown in Table 4 below.

[0077] As a result of Experimental Example 6, the strontium removal efficiency was 97.55% in Example 1, 71.10% in Comparative Example 1, and 16.0% in Comparative Example 2. The strontium removal efficiency was calculated according to Equation 1.

[0078] [Table 4]

[0079] Experimental Example 7. Color change after adsorption of strontium onto magnesium silicate Experimental Example 7 was carried out to observe the color change after strontium adsorption of the magnesium silicate and illite prepared in Example 1, Comparative Example 1 and Comparative Example 2. The strontium adsorption method using the magnesium silicate according to Example 1 was carried out in the same manner as in Experimental Example 6. The color change of the magnesium silicate after strontium adsorption is shown in FIG.

[0080] As a result of Experimental Example 7, no change in color was observed after strontium adsorption in the magnesium silicate and illite produced in Example 1, Comparative Example 1, and Comparative Example 2 (FIG. 3).

[0081] Experimental Example 8. Elemental content of magnesium silicate The magnesium silicate and illite prepared in Example 1, Comparative Example 1 and Comparative Example 2 were analyzed for elemental contents.

[0082] We used our own EMCRAFT SEM (CUBE II) and the attached EDS detector (Xplore compact 30) and AZtecOne program to perform a compositional analysis of magnesium silicate and illite.

[0083] As a result of this Experimental Example 8, the Mg:Si ratio of the magnesium silicate of Example 1 was 1:4.17, and the adsorption capacity of radioactive elements cesium, cobalt and strontium was the best at this ratio (Table 5). This is considered to be because a negative channel of oxygen atoms was formed between the layers of magnesium silicate, improving the adsorption capacity of cesium, cobalt and strontium (see FIG. 4). In the case of the illite produced in Comparative Example 2, the silicate ratio is high, but K, Fe and Al ions coexist, which is considered to lower the adsorption capacity of radioactive elements cesium, cobalt and strontium.

[0084] [Table 5]

[0085] Experimental Example 9. Analysis of adsorption capacity by ion size of radioactive elements Cesium (Cs + ), Cobalt (Co 2+ ) and strontium (Sr 2+ The ion sizes of radioactive elements such as cesium (Cs) are shown in Table 6 below, and the adsorption capacity according to the ion size is compared. + ) has an ion size of 169 pm, and cobalt (Co 2+ ) has an ion size of 72 pm, and strontium (Sr 2+ The ion size of cobalt (Co) was 113 pm. 2+ )< Strontium (Sr 2+ )<Cesium (Cs + ), so cobalt (Co 2+ It is concluded that the ionic radius of the ZnO ion is small and it is easy to get caught between the negative channels of magnesium silicate, resulting in high removal efficiency.

[0086] [Table 6]

[0087] Experimental Example 10. XRF Analysis of Magnesium Silicate The magnesium silicate and illite prepared in Example 1, Comparative Example 1, and Comparative Example 2 were subjected to XRF analysis, and the results are shown in Table 7.

[0088] [Table 7]

[0089] As a result of Experimental Example 10, the magnesium silicate of Example 1 was confirmed to be 14.5 wt% MgO and 72.5 wt% SiO2, the magnesium silicate of Comparative Example 1 was confirmed to be 15.4 wt% MgO and 70.6 wt% SiO2, and the illite of Comparative Example 2 was confirmed to be 13.9 wt% MgO and 80.9 wt% SiO2.

[0090] From the above description, those skilled in the art may realize that the present invention may be embodied in other specific forms without changing the technical spirit or essential characteristics of the present invention. In this regard, the above-described embodiments are illustrative in all respects and not restrictive.

Claims

1. A radioactive element adsorbent containing magnesium silicate, The pore diameter is 33-40 Å, the specific surface area is 40-60 m 2 / g, the pore volume is 0.02-0.1 cm 3 / g, and the Mg:Si ratio is 1:3-4; The radioactive elements to be adsorbed are cesium and strontium. A radioactive element adsorbent characterized by:

2. The magnesium silicate is Compared to USP / NF standard magnesium silicate, the MgO content is reduced by 3-4% and SiO 2 The content increased by 8 to 8.5%, The USP / NF standard magnesium silicate has an MgO content of 15% and an SiO2 content of 67%. A radioactive element adsorbent comprising the magnesium silicate of claim 1.

3. The magnesium silicate is The magnesium silicate contains 14.4 to 14.6 parts by weight of MgO relative to 100 parts by weight of the magnesium silicate, and SiO 2 Contains 72.4 to 72.6 parts by weight A radioactive element adsorbent comprising the magnesium silicate of claim 1.

4. (A1) adding tetraethyl orthosilicate (TEOS) to a mixture of alcohol, water and aqueous ammonia (NH 3 H 2 O, ammonia-water), stirring at 200-300 rpm for 1-3 hours, and drying at 60-80° C. to prepare a silicate precursor; (A2) dissolving magnesium chloride (MgCl 2 ) and ammonium chloride (NH 4 Cl) in distilled water, and then adding ammonia water (NH 4 OH) to prepare a mixture; (A3) adding the silicate precursor to the mixture, reacting at 120-160°C for 10-14 hours, and drying at a temperature of 60-80°C to produce a radioactive element adsorbent containing magnesium silicate; Includes A method for producing a radioactive element adsorbent containing magnesium silicate, comprising:

Citation Information

Patent Citations

  • Crystallized mesoporous magnesium silicate powder and preparation method thereof

    CN104495861A

  • Preparation method of strontium ion Sr&lt;2+&gt;-targeting adsorption material

    CN113274984A

  • Cesium removal method

    JP2015040833A

  • Plate-shape titanosilicate molecular sieve, method of preparing the same, and carbon dioxide absorbent including the same

    KR102221740B1

  • Disposable hazardous and radioactive liquid aqueous waste composition and method

    US4781860A